Fractional integration analysis of precipitation dynamics: empirical insights from Nigeria - O.O. Awe (Taylor & Francis Group, 2021)
This paper deals with the time series analysis of precipitation patterns in Africa’s most populated nation using recently developed flexible modelling techniques to study the monthly precipitation data of some major economically viable and highly populated regions in Nigeria. The results indicate that there is a significant trend for Lagos rainfall data, implying that precipitations have systematically increased over time in this city. Additionally, the seasonal component is more prominent in the cases of Kano and Kaunda than for Ibadan and Lagos. The findings of this study have relevant policy implications for forecasting, agricultural planning, relating precipitation variability in Nigeria with standard climate drivers, as well as for disaster or risk reduction in the context of climate change, global warming and migration in the post-pandemic era.